Ultrasonic instrument for accurate measurements of spatial parameters in blood vessels - Mani, Mohammad H. (2016)
The present research is aimed at the development of an ultrasonic medical instrument capable of measuring the intima-media thicknesses (IMT) of artery walls that are considered by medical practitioners as good indicators of the risk of atherosclerosis. This overcomes two notable limitations of the instruments available at present – insufficient axial resolution and lack of synchronisation to the heart cycle that make the measurements difficult to use, e.g., for annual screening of patients and like-for-like comparisons. These limitations were addressed by using a combination of on-the-fly averaging and interleaved sampling for acquiring echo waveforms, and triggering the scans at a particular instant of the heart cycle. The developed electronic instrumentation consisted of a battery powered electrocardiogram (ECG) monitor that transmitted the ECG data using an infrared link to the ECG processor that triggered the scans. Such architecture eliminated any possibility of accidentally connecting the patient to a source of voltage capable of causing serious injury and of causing radio frequency interference to medical equipment located in a close proximity. The algorithm for detecting the R-waves from noisy ECGs was fully verified with simulated and experimental ECG records, and implemented in firmware on board the ECG processor. The rate of R-wave detection of the developed algorithm is 88.24% out of 204 heartbeats recorded.